PENERAPAN PEMBUKTIAN SEDERHANA DALAM KEPAILITAN MENURUT UNDANG-UNDANG NO 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU (STUDI KASUS: PUTUSAN NOMOR: 04/PDT.SUS.PAILIT/2015/PN.NIAGA.JKT.PST)” - Rafael Angelo Dias; Suyud Margono (Jurnal Hukum Adigama, 2018)
In submitting a bankruptcy application, the applicant must submit evidence to prove the existence of a debt. The specialty of proof in the law of bitterness is the existence of simple proof, according to the juridical requirements as referred to in Article 8 paragraph (4) according to the juridical requirements as referred to in article 2 paragraph (1) of the bankruptcy law. This simple proof can also cause problems. One concrete form of the problem that arises in this simple verification in practice is the decision of the Commercial Court at the Central Jakarta District Court with the decision number: 04 / Pdt-Sus.Pailit / 2015 / PN.Niaga / JKT.PST between the Service Authority Commissioner Board and PT Asuransi Jiwa Bumi Asih Jaya. The problem is how to apply simple evidence in the case. This writing uses normative legal research methods which are based on primary data and secondary data which are analyzed descriptively with conceptual and legislative approaches. Based on the analysis according to Article 8 paragraph (4) in conjunction with Article 2 paragraph (1) UUKPKPU, it can be stated that the debt of PT Asuransi Jiwa Bumi Asih Jaya has been proven in a simple manner, but the Judges in the decision rejected the application on the grounds that the debt proof was not simple. 8 paragraph (4) UUKPKPU.